ANALISIS REKONSILIASI FISKAL DAN PERHITUNGAN PAJAK PENGHASILAN BADAN TERUTANG PADA PT XYZ - Saabitah Rizky Putri; Purnamawati Helen Wijaya (Universitas Prof.Hazairin,SH Bengkulu, 2026)
This research attempts to analyze this implementation from positive and negative fiscal corrections and to determine the amount of corporate income tax due of PT XYZ in 2023. This study employed a quantitative descriptive approach that makes use of secondary data in the form of the statement of financial position, income statement, and fiscal reconciliation documents of the company. The results indicate that PT XYZ recorded positive fiscal corrections of Rp911,485,000 and negative fiscal corrections of Rp30,090,000, resulting in taxable income before fiscal loss compensation of Rp1,916,527,000. Based on the company's calculation, the Corporate Income Tax Payable amounted to Rp67,391,000. However, based on the author's analysis, the entire taxable income could be offset by accumulated fiscal losses, resulting in zero Corporate Income Tax Payable. The study concludes that fiscal corrections and fiscal loss compensation affect The Corporate Income Tax Amount Due.